Controller design for Networked Control Systems—An approach based on L2 induced norm. (February 2016) - Halder, Kaushik; Das, Sourav; Dasgupta, Soumya; Banerjee, Shohan; Gupta, Amitava
Abstract: In this paper a Linear Matrix Inequality (LMI) based methodology has been presented to design a time-driven controller to control a plant over a network with random variable delay ( jitter ) and packet dropout. The system with controller and network is formulated as a system which switches arbitrarily between its constituent sub-systems due to data-loss and/or jitter. A LMI based approach is used and the LMI formulations presented in this paper use a disturbance attenuation level as a specification. Satisfaction of these LMIs indicate that the designed controller ensures that the system maintains the same disturbance attenuation level even under data-loss and/or jitter when controlled over a network. The methodology has been demonstrated with credible simulation and compared with results put forward by contemporary researchers.